2019
DOI: 10.1002/jssc.201900888
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantification of atractyloside and carboxyatractyloside in rat plasma by LC‐MS/MS: Application to a pharmacokinetic study after oral administration of Xanthii Fructus extract

Abstract: Xanthii Fructus is extensively used as an herbal medicine. Ingestion of this herb is associated with severe hepatotoxicity and nephrotoxicity. Atractyloside and carboxyatractyloside are two dominative toxic constituents in Xanthii Fructus. However, their pharmacokinetic study is lacking. In this study, a novel high-performance liquid chromatography-tandem mass spectrometry method was developed to simultaneously quantify the rat plasma concentrations of atractyloside and carboxyatractyloside. After protein prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Curiously, ATR and CATR display comparable properties in terms of their absorption rate and elimination half-life (studies using rats) (Pan et al. 2020 ). However, the contents of these glycosides and their proportions in crude versus processed herbal material may considerably differ and are related to the geographical location (effects of climate and soil composition), harvesting time (effects of aging and desiccation), and genetic factors (Santi 1958 ; Obatomi and Bach 1998 ; Daniele et al.…”
Section: Basics Of Atractyloside and Carboxyatractyloside Toxicities ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Curiously, ATR and CATR display comparable properties in terms of their absorption rate and elimination half-life (studies using rats) (Pan et al. 2020 ). However, the contents of these glycosides and their proportions in crude versus processed herbal material may considerably differ and are related to the geographical location (effects of climate and soil composition), harvesting time (effects of aging and desiccation), and genetic factors (Santi 1958 ; Obatomi and Bach 1998 ; Daniele et al.…”
Section: Basics Of Atractyloside and Carboxyatractyloside Toxicities ...mentioning
confidence: 99%
“…2020 ; Pan et al. 2020 ). Additionally, variation in sampling and detection methods explains the incredibly large discrepancies in the ATR/CATR concentrations among the different parts of a tested plant (described above for Xanthium spp.)…”
Section: Basics Of Atractyloside and Carboxyatractyloside Toxicities ...mentioning
confidence: 99%
“…It has been reported that the simultaneous analysis of the above nine TKIs using HPLC–diode array detection (DAD) required a running time of 17.5–35 min [8–11]. LC–MS and LC–MS/MS have high analytical SEN [12–14]. However, they are expensive, have high maintenance costs, and need professional technicians to operate.…”
Section: Introductionmentioning
confidence: 99%